EXPRESSION OF NATIONAL VALUES IN ENGLISH AND UZBEK WEDDING CEREMONY DISCOURSE - Umurova Khushvakht Hakimovna (International Journal of Literature and Language Studies, 2026)
Wedding ceremonies represent one of the most important cultural institutions through which societies preserve, transmit, and reinforce their national values. The discourse surrounding wedding ceremonies reflects not only linguistic traditions but also social norms, cultural beliefs, historical experiences, and collective identities. In both English-speaking and Uzbek societies, wedding discourse functions as a communicative medium through which concepts such as family, respect, love, responsibility, social solidarity, and cultural continuity are expressed and maintained. Despite the influence of globalization and modernization, wedding ceremonies continue to preserve many traditional elements that embody national values. This study explores the expression of national values in English and Uzbek wedding ceremony discourse through a comparative linguistic and cultural analysis. The research examines verbal rituals, ceremonial speeches, blessings, congratulatory expressions, symbolic language, and communicative practices associated with weddings. The findings reveal that while both cultures emphasize family unity, commitment, and social harmony, significant differences exist in the ways these values are linguistically and pragmatically represented. Uzbek wedding discourse demonstrates a stronger collectivist orientation, whereas English wedding discourse reflects a greater emphasis on individual choice and personal happiness.